FORMULATION AND EVALUATION OF MEFENAMIC ACID OINTMENT USING PENETRATION ENHANCERS - KHAN, YOUSAF; JAN, SYED UMER; GUL, RAHMAN (International Journal of Current Pharmaceutical Research, 2020)
Objective: The aim of study was to formulate and evaluate Mefenamic acid ointment by the addition of penetration enhancer’s clove oil. Methods: 1%, 2% and 3% formulations of Mefenamic acid ointment formulated as per B. P, by melting hard paraffin 4.75g at 60 °C initially and to this 4.75 g wool fatwas incorporated, followed by addition of soft paraffin 80.75g and then adding Cetostearyl alcohol 4.75g and 1,2 and 3 ml clove oil by continuous stirring later on ointment being cooled at room temperature. These formulations were checked for consistency, Spreadability, homogeneity, PH, viscosity, skin irritation, drug content, UV absorbance, Differential scanning calorimetry (DSC) and XRD (X. ray diffraction) studies. In vitro pattern via using Franz cells besides with the use of dialysis cellulose membrane was done. Results: All the synthesized formulations illustrated fine physicochemical characteristics. SEM and XRD Studies expressed that there were no physicochemical incompatibilities among active ingredient (Mefenamic acid salt) and additives combined as drug permeation enhancers (clove oil).3% formulation showed maximum released 65.199%. Conclusion: In the present study, it was noted that clove oil can enhance the permeation of Mefenamic acid topical ointment.